ANALISIS KINERJA REKSADANA SYARIAH DI PASAR MODAL INDONESIA MENGGUNAKAN METODE SHARPE - Raudhah Trisna Wardhani; Ahmad Juanda; Dhaniel Syam (Jurnal Akademi Akuntansi, 2018)
The purpose of this study is to analyze the performance of Islamic mutual funds that include stocks, fixed income, mixes, and money markets using Sharpe method. The type of research conducted is quantitative descriptive research. Data collection method in this research is documentation technique with secondary data that is through official website bareksa.com. In performance measurement, in this research, the researcher only use one method only that is a method of shape. The performance of mutual funds using this shaping method can be analyzed using three indicators; the rate of return of mutual fund, the risk of a mutual fund with standard deviation, a method of shape. Based on the calculation of Sharpe can be concluded that the highest performance among Islamic mutual funds that include stocks, fixed income, mix and money market in 2015, 2016, 2017 is sharia mutual fund shares. Sharia mutual fund shares can be said to be the highest because in the three performance indicators mentioned above mutual funds sharia shares obtain the highest results when compared with other types of mutual funds sharia.